'It's not me, it's them' - a report describing the weight-related attitudes towards obesity in pregnancy among maternal healthcare providers - Taniya S. Nagpal; Kirina Angrish; Emily Bonisteel; Rebecca M. Puhl; Zachary M. Ferraro; Niyati M. Malkani; Caroline LeJour; Kristi B. Adamo (BMC, 2024)
Abstract Background Occurrences of weight stigma have been documented in prenatal clinical settings from the perspective of pregnant patients, however little is known from the viewpoint of healthcare providers themselves. Reported experiences of weight stigma caused by maternal healthcare providers may be due to negative attitudes towards obesity in pregnancy and a lack of obesity specific education. The objective of this study was to assess weight-related attitudes and assumptions towards obesity in pregnancy among maternal healthcare providers in order to inform future interventions to mitigate weight stigma in prenatal clinical settings. Methods A cross-sectional survey was administered online for maternal healthcare providers in Canada that assessed weight-related attitudes and assumptions towards lifestyle behaviours in pregnancy for patients who have obesity. Participants indicated their level of agreement on a 5-point likert scale, and mean scores were calculated with higher scores indicating poorer attitudes. Participants reported whether they had observed weight stigma occur in clinical settings. Finally, participants were asked whether or not they had received obesity-specific training, and attitude scores were compared between the two groups. Results Seventy-two maternal healthcare providers (midwives, OBGYNs, residents, perinatal nurses, and family physicians) completed the survey, and 79.2% indicated that they had observed pregnant patients with obesity experience weight stigma in a clinical setting. Those who had obesity training perceived that their peers had poorer attitudes (3.7 ± 0.9) than those without training (3.1 ± 0.7; t(70) = 2.23, p = 0.029, Cohen's d = 0.86). Conclusions Weight stigma occurs in prenatal clinical environments, and this was confirmed by maternal healthcare providers themselves. These findings support advocacy efforts to integrate weight stigma related content and mitigation strategies in medical education for health professionals, including maternal healthcare providers. Future work should include prospective examination of weight related attitudes among maternal healthcare providers and implications of obesity specific education, including strategies on mitigating weight stigma in the delivery of prenatal care.